The READ-IT study protocol for a feasibility randomised controlled trial of using a support worker/family carer mediated online reading programme to teach early reading skills to adults with intellectual disabilities - Gwenllian Moody; Elinor Coulman; David Gillespie; Mark Goddard; Corinna Grindle; Richard P. Hastings; Carl Hughes; Kate Ingarfield; Zac Taylor; Louise Denne (Pilot and Feasibility Studies, 2022)
Abstract Background Many individuals with intellectual disability (ID) have not learnt basic reading skills by the time that they reach adulthood, potentially limiting their access to critical information. READ-IT is an online reading programme developed from the Headsprout® Early Reading (HER®) intervention and supplemented by support strategies tailored for adults with ID. HER® has been successfully used to teach adults with ID to read in a forensic setting by trained staff. The aim of this study is to assess the feasibility of delivering READ-IT to adults with ID by family carers/support workers and will assess whether it would be feasible to conduct a later definitive randomised controlled trial (RCT) of the effectiveness of the programme. The study will aim to contribute to the evidence base on improving outcomes for adults with ID and their caregivers. Methods This study is a feasibility RCT, with embedded process evaluation. Forty-eight adults with ID will be recruited and allocated to intervention: control on a 1:1 basis. Intervention families will be offered the READ-IT programme immediately, continuing to receive usual practice and control participants will be offered the opportunity to receive READ-IT at the end of the trial follow-up period and will continue to receive usual practice. Data will be collected at baseline and 6 months post-randomisation. Discussion The results of this study will inform a potential future definitive trial, to evaluate the effectiveness of READ-IT to improve reading skills. Such a trial would have significant scientific impact internationally in the intellectual disability field. Trial registration ISRCTN11409097